The Relationship Between Physical Activity Levels, Nutritional Status, and Preschool Child Development - Helen Lucky Maharani; Ahmad Suryawan; Widati Fatmaningrum (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction:The preschool a long time are a basic stage in a child's advancement. Agreeing to the World Wellbeing Organization (WHO, 2021), the predominance of formative clutters is higher in moo- and middle-income nations. In Indonesia, the child improvement list stands at 88.3%, which is lower than Thailand (93%) and Laos (89%) . Furthermore, around 6.5 million out of 22 million children under five are not monitored for growth and development. Both growth and development are closely interrelated, with factors like physical activity and nutritional status playing key roles in ensuring optimal development. Objective: This consider points to analyze the relationship between physical movement levels, wholesome status, and child improvement in preschool-aged children . Methods: An observational, cross-sectional study was conducted at a Posyandu (community health center) with 82 children who met the inclusion criteria. Purposive sampling was used. Data were collected through a 24-hour physical activity recall, anthropometric measurements (weight and height) to assess nutritional status, and the Pre-Screening Developmental Questionnaire (KPSP) to evaluate child development. Results: Spearman's test uncovered a noteworthy relationship between physical movement and child improvement (P = 0.001, r = 0.380), as well as a more grounded relationship between wholesome status and child improvement (P = 0.001, r = 0.610). Conclusion: Higher levels of physical action and way better dietary status are emphatically related with age-appropriate child improvement. These discoveries highlight the significance of advancing physical action and appropriate sustenance for supporting ideal improvement in preschool-aged children.